Innovation capability of MSMEs : do social capital, tecnological capital, customer capital, and social media networking matters? - Tiara Meilan Putri; Bima Cinintya Pratama; Novi Dirgantari; Annisa Ilma Hartikasari (Jurnal Mantik, 2023)
MSMEs or Micro Small and Medium Enterprises are the primary of national economic growth. In developing and advancing Indonesian MSMEs, support from various elements is certainly needed, starting from funding, licensing, protecting, and coaching to adequate logistics services. Including the ability to innovate which has an impact on increasing the potential of MSMEs.The development of MSMEs depends heavily on their capacity for innovation, which must be owned by MSME perpetrators if MSMEs are to remain competitive and profitable. In order to preserve its commercial worth, a MSMEs is also effect by elements related to intellectual capital. Therefore, the purpose of this study is to evaluate the impact of intellectual capital and social media networking on innovation capability. This study used MSMEs in the Banyumas, Brebes, and Cilacap Regencies of Central Java. SEM-PLS is the data analysis method applied in this study. Through improved innovation and business development, it is anticipated that this research will be able to strengthen MSMEs capabilities. According to the study's findings social capital, technological capital, customer capital, and social media networking all positively impact an organization's capacity for innovation